(untitled) (Web of Teachers: Inderscience Research, 2026)
This article discusses the pedagogical and methodological foundations of the formation and development of creative thinking skills in future music teachers. The importance of a creative approach in the process of music education, the impact of innovative teaching methods, interactive methods and types of musical activities on creative thinking are analyzed. Also, effective ways to develop creative thinking in improving the professional competence of future specialists are proposed.